PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SAMSUNG GALAXY SERIES J DI KOTA SEMARANG - Nur Atika Ramawati; Agung Budiatmo (Jurnal Ilmu Administrasi Bisnis, 2018)
The purpose of this study is to determine the effect of product quality, brand image, and price to the purchase decision of Samsung Galaxy Series J in Semarang City. This type of research is explanatory research. Sampling technique using non probability sampling technique with purposive sampling and Accidental sampling method. The number of samples taken as many as 100 respondents. In this study assisted by SPSS 16.0 system. The results showed that the quality of the product influence the purchase decision by contributing 61.8% while the rest is influenced by factors other than product quality. Brand image influences purchasing decisions by contributing 33.7% while the rest is influenced by factors other than brand image. Price affects purchasing decisions by contributing 63.1% while the rest is influenced by factors other than price. Meanwhile, simultaneously product quality, brand image, and price influence to purchase decision by donating 77,2% while the rest influenced by factors other than product quality, brand image, and price. Based on the calculation of Test F shows that there is a positive influence between product quality, brand image and price to purchase decision. This means the better the product quality, brand image and price, the higher the purchase decision of Samsung Galaxy Series J in Semarang City. In addition, the price has the most dominant influence with regression keofisien value of 0.733. Suggestions in this research is to improve the quality of the better and more sophisticated products, maintaining the company's image in the minds of the constituents and provide prices that match the benefits provided on the Samsung Galaxy J Series.